PROFITABILITAS DARI SUDUT PANDANG TATA KELOLA YANG BAIK DAN UKURAN PERUSAHAAN - Novyarni, Nelli; Pratiwi, Amreiza; Harni, Reni; Kartijo (Jurnal Akuntansi, 2025)
In this study, we will analyse the consumer goods, basic materials, and chemicals sectors for companies listed on the Indonesia Stock Exchange from 2020 to 2022. We will look at how firm size and effective corporate governance affect profitability.   E-Views 12 panel data regression analysis and descriptive quantitative methods are used in this investigation.   Participants in the research include companies that were listed on the IDX between 2020 and 2022 and belong to the consumer products, basic materials, and chemicals sectors.  The sample, which consisted of 71 firms and yielded 213 observations in total, was selected using a purposeful selection method.   This inquiry makes use of secondary sources of information.  For the purpose of documenting the data gathering process, the official websites of the company and IDX (www.idx.co.id) are used.   Based on the study's findings, we can say that “(1) managerial ownership has a positive and significant effect on profit, (2) constitutional ownership does not affect profit, (3) an independent board of commissioner ownership has a positive and significant effect on profit, (4) the audit committee ownership has a positive and significant effect on profit , and (5) the size of the company ownership has a positive and significant effect on profit”.  Keywords :  Ownership, Independence Board of commissioners, Audit Committee, Company Size, Profitability